Phylogeny of Anatolian (Turkey) species in the Digitalis sect. Globiflorae (Plantaginaceae) - Eker, İsmail; Yücesan, Buhara; Sameeullah, Muhammad; Welß, Walter; Müller-Uri, Frieder; Gürel, Ekrem; Kreis, Wolfgang (Phytotaxa, 2016)
This study analyses phylogenetic and morphological relationships regarding the taxonomy of Digitalis sect. Globiflorae. Progesterone 5β-reductase (P5βR) is an important enzyme for cardenolide biosynthesis as well as a novel genetic marker inferring phylogenetic and biogeographic relationships in many plant species. Phylogenetic inference was conducted using the neighbor-joining method and maximum likelihood model on cDNA sequences of highly conserved P5βR (97.0–99.6%) isolated from members of sect. Globiflorae, including Digitalis trojana, D. cariensis, D. lamarckii, D. lanata subsp. lanata, D. ferruginea subsp. ferruginea and D. ferruginea subsp. schischkinii. Our phylogenetic and morphological results largely support Davis’ system of the genus Digitalis in the Flora of Turkey. We propose the existence of four species and three subspecies in sect. Globiflorae for Turkey. Digitalis cariensis is a distinct species endemic to Turkey. In spite of high morphological similarities, D. lamarckii was separated from D. trojana and D. lanata. Digitalis trojana is accepted at the infraspecific rank as D. lanata subsp. trojana. In addition, D. ferruginea is ranked under the two subspecies following Werner’s treatment. Our study presents a new understanding of the speciation patterns of endemic and non-endemic eastern Digitalis species distributed in Anatolia, Turkey, underlying molecular, biogeographical and comparative morphological analyses.